The digitized First Byurakan Survey database. New carbon stars confirmed - Gigoyan, K. K.
Some amount of the new carbon ( C ) stars was confirmed among the sample of the Late-Type Stars (LTSs) candidates, selected on the Digitized First Byurakan Survey (DFBS) spectral plates. The DFBS is the digitized version of the First Byurakan Survey (FBS, or Markarian survey). The FBS was the first systematic survey of the extragalactic sky. This objective-prism survey was carried out in 1965-1980 by B. E. Markarian and colleagues using the 1 m Schmidt telescope of the Byurakan Astrophysical Observatory. In this work we present Gaia DR3 photometric data, spectra, light curves, distances, high above/below Galactic plane, radial velocities (RV), and other important physical characteristics from modern astronomical catalogues for some amount new confirmed DFBS carbon stars. The confirmation is based on Gaia DR3 BP/RP low-resolution spectral database. In previous studies of the DFBS plates, these objects were presented as LTSs candidates. Some objects are located more than 7 kpc from the Galactic plane. Four of them are N-type C stars, from which two are Mira-type variables. The remaining objects are CH-type giants at high Galactic latitudes. Most probably they present binary systems.
Keywords: Astrometry; Space Sciences; Archaeoastronomy and Astronomy in Culture